Low-depth shotgun sequencing resolves complete mitochondrial genome sequence of Labeo rohita. (2nd September 2016) - Das, Sofia P.; Bit, Amrita; Patnaik, Siddhi; Sahoo, L.; Meher, P. K.; Jayasankar, P.; Saha, T. M.; Patel, A. B.; Patel, Namrata; Koringa, P.; Joshi, C. G.; Agarwal, Suyash; et al.
Abstract: Labeo rohita, popularly known as rohu, is a widely cultured species in whole Indian subcontinent. In the present study, we used in-silico approach to resolve complete mitochondrial genome of rohu. Low-depth shotgun sequencing using Roche 454 GS FLX (Branford, Connecticut, USA) followed by de novo assembly in CLC Genomics Workbench version 7.0.4 (Aarhus, Denmark) revealed the complete mitogenome of L. rohita to be 16 606 bp long (accession No. KR185963). It comprised of 13 protein-coding genes, 22 tRNAs, 2 rRNAs and 1 putative control region. The gene order and organization are similar to most vertebrates. The mitogenome in the present investigation has 99% similarity with that of previously reported mitogenomes of rohu and this is also evident from the phylogenetic study using maximum-likelihood (ML) tree method. This study was done to determine the feasibility, accuracy and reliability of low-depth sequence data obtained from NGS platform as compared to the Sanger sequencing. Thus, NGS technology has proven to be competent and a rapid in-silico alternative to resolve the complete mitochondrial genome sequence, thereby reducing labors and time.